Orientation of musical disciplines as a condition for the formation of competencies - Anufrieva, Natalia; Avramkova, Irina; Anna Shcherbakova, Irina Korsakova, Marina Pereverzeva, (Opción, 2019)
The article reveals the essence and specificity of the concept professional training of a specialist in the musical sphere, highlights its fundamental aspects via analysis of philosophical, psychological, pedagogical and special literature on the studied problem. As a result, the concept of a specialty orientation of musical disciplines is considered as a condition for the formation of key competences of specialists in the area of culture and the art areas. In conclusion, the orientation of the entire educational complex to the ultimate goal of the student preparation process is a condition for the implementation of the modern education paradigm